2023
DOI: 10.17583/redimat.12884
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Student Engagement and Motivation in the Statistics Learning Process

Jitu Halomoan Lumbantoruan

Abstract: The aim of the present exploratory study was to examine students’ situational engagement and motivation in the statistics classroom at Zayed University, in Dubai, United Arab Emirates (UAE). Two instruments were used for this purpose: a) experience sampling method (ESM), and b) the validated Mathematics Motivation Questionnaire (MMQ). This study employed two samples, at undergraduate level (2nd and 4th Semesters). Participants consisted of 100 students enrolled in Statistics I and Statistics II (Probability an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…In line with the phenomenon of learning difficulties, the results of research conducted showed that junior high school students had not fully achieved good learning outcomes in comparative material (Dahlin & Watkins, 2000;Halomoan Lumbantoruan, 2023). Many students still have difficulty solving story problems.…”
Section: Introductionmentioning
confidence: 98%
“…In line with the phenomenon of learning difficulties, the results of research conducted showed that junior high school students had not fully achieved good learning outcomes in comparative material (Dahlin & Watkins, 2000;Halomoan Lumbantoruan, 2023). Many students still have difficulty solving story problems.…”
Section: Introductionmentioning
confidence: 98%